Neighborhood socioeconomics, food environment and land use determinants of public health: Isolating the relative importance for essential policy insights. (November 2017) - Zhou, Min; Tan, Shukui; Tao, Yinghui; Lu, Yongzhong; Zhang, Zuo; Zhang, Lu; Yan, Danping
Abstract: Recent literature has advocated the connection between land use policies with public health promotion. In this regard, examining the land use determinants of public health and isolating the relative importance with other influential factors should provide essential policy insights. However, very limited efforts have been made in this aspect, particularly for the developing countries. Using a case of Wuhan (China), this paper attempts to capture the land use determinants of obesity prevalence among middle-aged adults and to compare the relative importance with neighborhood socioeconomics and food environment. A conceptual framework is first proposed to guide the analysis within a land use policy context. Data are then collected during the China's National Physical Fitness Survey in 2010 and multivariate linear regression is applied to analyze the district level determinants. Results show that neighborhood socioeconomics, food environment and land use all have significant effects on obesity prevalence among the middle-aged adults. The men obesity is associated with the occupation, education and housing, while women obesity is correlated with income and housing. Women obesity associates with healthy food environment, while men obesity correlates with unhealthy food environment. Open public space is negative to women obesity, and institutional land is negative to men obesity. Greater walkability and street connectivity associate with lower obesity risk for both genders. The variance decomposition demonstrates that food environment is the most important determinant of men obesity, while land use is the most essential determinant of women obesity. For the obesity prevalence among total population, neighborhood socioeconomics are key determinants. Based on our analysis, we finally provide some insights for land use policies that aim at addressing the obesity issue in developing countries.